2011
DOI: 10.1016/j.jccase.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Isolated ACTH deficiency presenting with severe myocardial dysfunction

Abstract: We present a case of isolated adrenocorticotropic hormone (ACTH) deficiency complicated by acute adrenal crisis and severe myocardial dysfunction. A 54-year-old woman developed consciousness disturbance, hypoglycemia, hyponatremia, and rhabdomyolysis. Initial echocardiographic examinations on the sixth hospital day revealed marked right-sided atrial and ventricular dilatation and severe tricuspid regurgitation. A computed tomography scan for pulmonary embolism was negative. On the 14th hospital day, she became… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Additionally, LV dysfunction rarely occurs with adrenocortical insufficiency. Previous reports have indicated that severe myocardial dysfunction is an uncommon but serious complication of adrenal insufficiency . In such cases, electrocardiographic and echocardiographic abnormalities normalized after steroid replacement therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, LV dysfunction rarely occurs with adrenocortical insufficiency. Previous reports have indicated that severe myocardial dysfunction is an uncommon but serious complication of adrenal insufficiency . In such cases, electrocardiographic and echocardiographic abnormalities normalized after steroid replacement therapy.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to these common causes, there are other rare causes of left‐sided congestive heart failure. There are a few reports of left ventricular (LV) dysfunction caused by isolated adrenocorticotrophic hormone (ACTH) deficiency . Isolated adrenocorticotrophic hormone deficiency is a rare cause of secondary adrenocortical insufficiency and is difficult to diagnose .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the glucocorticoids deficit reduces the expression of adrenergic receptors and adrenalin synthesis and affects the cardiovascular reactivity to catecholamines. These mechanisms could explain the severe myocardial dysfunction associated to adrenal insufficiency ( 15 ). However, we could not identify animal studies explaining mechanisms associated with the occurrence of acute coronary syndrome in adrenal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal insufficiency has also been associated with transient left ventricular apical ballooning known as Takotsubo cardiomyopathy. This type occurs exclusively in adult patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%